DISTRIBUSI DAN KEMELIMPAHAN KOMUNITAS HEWAN TANAH DI HUTAN PEGUNUNGAN KAMOJANG JAWA BARAT - , RADILIKA CHANDRA M D; , Dr. Tjut Sugandawaty Djohan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was to study the distribution and abundance of soil animals at natural and disturbed tropical mountain forest in Kamojang geothermal area at above 1300 msl, West Java. The natural forest was secondary forest and had 5 layers. The disturbed forest had big gap-area. At each location we extracted the soil animals used Tullgren funnel methods with 10 replicates. The parameter measures were: animal density, soil temperature, soil moisture, pH, humidity, light intensity, and soil nutrients: NO3, NH4, PO4, K+, C, and organic matter. The result showed that there were 4 functional groups: saprophytic feeders, carnivores, phytophagus feeders and microphytic feeders, around in consecutively between 52-62% 16-27%, 6-14% and 6- 19%. The highest density for functional group of soil animals in nature and disturbed forest is saprophytic feeders 77-234/4,2dm3. However the species at each location reflected the type of plant species of vegetation. Almost of species at natural and disturbed tropical mountain forest was similar. Therefore the community of soil animals at Kamojang mountain forest were not indicator of forest conditions. Functional group saprophytic feeders consisted of 12-22 species, carnivores 7-12 species, phytophagus feeders 5-13, and microphytic feeders 2-5 species. The presence of soil animalâs community depended on plant species of vegetation at tropical mountain forest Kamojang.